Political Implications of Turkey – Qatar Gas Pipeline Construction on European Union Energy Security - Ingpraja, Ariscynatha Putra (Journal of International Relations on Energy Affairs, 2020)
This paper will discuss the political implication caused by Turkey-Qatar Gas Pipeline to the European Union energy security. The development of a logistics facility in this program could be a double-edged sword for the European Union member. Using realism as the leading theory that emphasizes politics as the main power to gain the state's national interest, writers try to build analytical case studies. With its hold of the logistics facility, Turkey could control the distribution of natural gas exporting to Europe. European Union members need to import natural gas to strengthen the energy security sector of their lack of energy sources. Through the dependency energy sources created by both actor, this will affect the European Union energy security, notably, by the facility owner's state.